Characterization of Microbubbles Generated in a Venturi Tube via Image Processing: Effect of Operating Parameters - Mera-Campo, Jhonnatan Stiven; Muñoz-Alegría, Jeimmy Adriana; Flórez-Marulanda, Juan Fernando; Muñoz-España, Elena (Ingeniería, 2023)
Context: This research developed a dissolved air flotation system using a Venturi tube to produce microbubbles. The Venturi tube replaces the saturation tank and the pressure-reducing valve of conventional systems. Method: The system has both suction and injection air inlets, regulates the recirculation flow of the liquid to the tank, and provides a high hydraulic load in a reduced size. Counting and measuring the microbubbles produced via digital image processing helps to characterize the system's performance. Results: The system with air suction produces smaller bubbles than that with air injection. A higher liquid recirculation pressure produces more bubbles and reduces their size in the case of air suction. Conclusions: In air injection, the change in flow rate influences the size of the microbubbles. Air injection and recirculation pressure do not influence the number of bubbles generated.